On Generalized Moduli of Quasi-Banach Space - Young Chel Kwun; Hussain Minhaj Uddin Ahmad Qadri; Waqas Nazeer; Absar Ul Haq; Shin Min Kang (Journal of Function Spaces)
We shall discuss three generalized moduli such as generalized modulus of convexity, modulus of smoothness, and modulus of Zou-Cui of quasi-Banach spaces and give some important properties of these moduli. Furthermore, we establish relationships of these generalized moduli with each other.